Sasanian archaeology : settlements, environment and material culture - Simpson, St John (Archaeopress Archaeology, 2022)
This collection of essays offers an examination of the Sasanian empire based almost entirely on archaeological and scientific research, much presented here for the first time. The book is divided into three parts examining Sasanian sites, settlements and landscapes; their complex agricultural resources; and their crafts and industries.